STRENGTHENING ACADEMIC SUPERVISION BASED ON COACHING CLINIC AT THE JUNIOR HIGH SCHOOL/MTs LEVEL IN PIDIE ACEH - Rasyid, Suparta; Usman, Nasir Usman; Niswanto, Niswanto; Murniati, murniati AR; ismail, ismail; Bahrun, Bahrun (Jurnal Pengabdian Bangsa, 2023)
The low quality of the learning process is still a challenge in efforts to improve the quality of education, especially at the educational unit level. This problem has an impact on the achievement of student learning outcomes and the effectiveness of learning activities in the classroom. One strategy that can be used to overcome this problem is the implementation of clinical supervision. Clinical supervision is a professional development approach that focuses on improving teacher learning practices in a collaborative, reflective, and sustainable manner. This community service activity aims to improve teacher competence in designing, implementing, and evaluating the learning process through clinical supervision guidance. The methods used in this activity include training, direct mentoring in the classroom, observation, and reflective discussions between supervisors and teachers. The results of the activity showed an increase in teacher understanding of the principles of clinical supervision and positive changes in the implementation of learning. Thus, clinical supervision has proven effective as a solution to improving the quality of the learning process as a whole.